MENELISIK INDUSTRI DAN STRUKTUR PASAR MEDIA MASSA DI INDONESIA - Permana, Rangga Saptya Mohamad; Suzan, Nessa (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2018)
Competition in the business and mass media industry globally began to be felt in Indonesia. This is evident in the structure of the mass media market in Indonesia, where media conglomeration has become commonplace. The industry and structure of the mass media in Indonesia has developed with many variants of mass media that can be consumed by audiences, whether they are conventional media types (old media) or internet based digital media (new media). The purpose of the research in this article is to find out the reality of industry and the structure of the mass media market in Indonesia. The research in this article uses qualitative research methods, precisely the descriptive-qualitative method, by focusing data from the literature review. The results of the research show that industrial conditions and the structure of the mass media market in Indonesia can be viewed from several perspectives, i.e. the number of media buyers and sellers, product differentiation, and barriers to competition. Meanwhile, to explore the structure of the mass media market in Indonesia, we can use The Theory of The Firm, which consists of four types of markets. The four types of markets are monopoly market, oligopoly market, monopolistic competition market, and perfect competition market. Media management from an art perspective can be used as a basis for the media industry; and globally, industry and the structure of the mass media market in Indonesia are not much different from other countries that adhere to the ideology of democracy in the world.